The sense of space - Morris, David, 1967- (Albany : State University of New York Press, 2004)
The Sense of Space brings together space and body to show that space is a plastic environment, charged with meaning, that reflects the distinctive character of human embodiment in the full range of its moving, perceptual, emotional, expressive, developmental, and social capacities. Drawing on the philosophies of Merleau-Ponty and Bergson, as well as contemporary psychology to develop a renewed account of the moving, perceiving body, the book suggests that our sense of space ultimately reflects our ethical relations to other people and to the places we inhabit.
Intro -- THE SENSE OF SPACE -- CONTENTS -- PREFACE -- LIST OF ABBREVIATIONS -- INTRODUCTION: THE PROBLEM OF DEPTH -- PART I: THE MOVING SENSE OF THE BODY -- 1. THE MOVING SCHEMA OF PERCEPTION -- 2. DEVELOPING THE MOVING BODY -- 3. THE TOPOLOGY OF EXPRESSION -- PART II: THE SPATIAL SENSE OF THE MOVING BODY -- 4. ENVELOPING THE BODY IN DEPTH -- 5. RESIDING UP AND DOWN ON EARTH -- 6. GROWING SPACE -- CONCLUSION: SPACE, PLACE, AND ETHICS -- NOTES -- INTRODUCTION -- CHAPTER 1 -- CHAPTER 2 -- CHAPTER 3 -- CHAPTER 4 -- CHAPTER 5 -- CHAPTER 6 -- CONCLUSION -- REFERENCES -- INDEX -- A -- B -- C -- D -- E -- F -- G -- H -- I -- J -- K -- L -- M -- N -- O -- P -- R -- S -- T -- U -- V -- W -- Z.
Includes bibliographical references (pages 197-213) and index.
Print version record.
English.
eBooks on EBSCOhost
Keywords: Merleau-Ponty, Maurice, -- 1908-1961.; Merleau-Ponty, Maurice, -- 1908-1961; Phénoménologie de la perception (Merleau-Ponty, Maurice); Human body (Philosophy); Movement (Philosophy); Space perception; Space Perception; Corps humain (Philosophie); Mouvement (Philosophie); Perception spatiale; space perception; PHILOSOPHY -- Epistemology; Human body (Philosophy); Movement (Philosophy); Space perception